Evaluación superficial del pavimento del Paso Lateral de Loja - Sanmartín Vargas, Juan Carlos (2018)
Abstract:The objective of this paper is the superficial evaluation of the Paso Lateral de Loja constituted by rigid pavement, the georeferencing of existing faults by obtaining the Pavement Condition Index (PCI). The methodology applied is that described in standard ASTM D6433-11. Inspections are carried out at the project level, selecting random units identifying faults, severity and quantity for each study unit. Applying the procedure of the mentioned regulation, it is obtained that for the stretch of track of 14.66 km of length 4 lanes and rigid pavement, it results an average PCI of 78.8 (very good state). The TPDA (Annual Average Daily Traffic) is also obtained and analyzed in the same way, which results in 3086 mixed vehicles / day to relate it to the PCI, which generates a historical data base on the operational evolution of the pavement. An intervention proposal is proposed according to the type of failure and its severity, based on the documents of the National Concrete Pavement Technology Center and Iowa State University Institute for Transportation.